Faktor-Faktor Yang Mempengaruhi Manajemen Laba Perusahaan Manufaktur - Riski Kurniawan; Fuad Fuad (Politeknik Ganesha Medan, 2022)
Earnings management is influenced by good corporate governance, leverage and audit quality. This study was conducted to prove empirically the results of the influence of managerial ownership, institutional ownership, board of commissioners, audit committee, leverage, audit quality and control variables profitability. The sample collection method used is purposive sampling. Secondary data obtained from the annual financial statements period 2017-2021 with certain characteristics. Samples were obtained from idx.co.id or obtained directly from the company's official website. The samples that have been collected in this study are 110 companies that meet all the criteria. The analytical technique used is multiple linear regression analysis and data processing tools using the SPSS v26. The results of this study indicate that based on the test results it can be concluded that the size of the audit committee has a positive effect on earnings management. Managerial ownership and the size of the board of commissioners have a negative effect on earnings management. Institutional ownership, leverage and audit quality have no effect on earnings management. While the profitability control variable has a positive effect on earnings management. Further research is suggested to expand the sample by taking financial or non-financial samples. Further research is also suggested to replace the method of measuring the variables of the board of commissioners and audit quality with other measurement methods.